The Pengembangan Model Pembelajaran Blended Learning Berbasis Edmodo Untuk Pembelajaran Kimia yang Efektif - Fadloli, Muhammad; Kusuma, Ersanghono; Kasmui, Kasmui (Universitas Negeri Semarang, 2019)
This study aims to develop an edmodo-based blended learning model in learning redox material and nomenclature compound, know the properness the media and see the effectiveness of the media toward the result of the students’ cognitive learning. The excellence of edmodo media is learning can be done anywhere and anytime. The research method used is research and development method with ADDIE development model, that is: 1. analysis (potential and problem analysis; 2. design (designing edmodo); 3. Development (developing edmodo media); 4. implementation (apply edmodo media to school); 5. evaluation (provide an assessment). The data were collected using expert validation sheet, teacher and student response questionnaire, and cognitive test question. The result of this research is obtained are one expert media and two expert materials in a row to reach the percentage of 86.36, 93.75, and 79.17% with very feasible criteria. The evaluation results of teachers, students of small and large scale test reached the percentage of feasibility of 77.50, 74.64 and 74.93% with attractive criteria. The students' cognitive learning outcomes after using edmodo as a learning medium reached the percentage of classical completeness 89.89%. The conclusion of this research is the learning model based on Edmodo-based blended learning is appropriate to be used as a medium of learning redox material and material nomenclature and it is also effective for students’ cognitive learning outcomes.